2017
DOI: 10.1007/s40264-016-0491-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Facebook and Twitter Monitoring to Detect Safety Signals for Medical Products: An Analysis of Recent FDA Safety Alerts

Abstract: IntroductionThe rapid expansion of the Internet and computing power in recent years has opened up the possibility of using social media for pharmacovigilance. While this general concept has been proposed by many, central questions remain as to whether social media can provide earlier warnings for rare and serious events than traditional signal detection from spontaneous report data.ObjectiveOur objective was to examine whether specific product–adverse event pairs were reported via social media before being rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
113
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(115 citation statements)
references
References 39 publications
1
113
0
1
Order By: Relevance
“…The EMA’s Eudravigilance database and the World Health Organization’s Vigibase contain vast numbers of drug reaction reports that can be screened to detect signals. Informal social media reports may uncover novel adverse drug reactions14 and help to understand serious reactions from the patient’s perspective 15…”
Section: How Are New Adverse Drug Reactions Uncovered?mentioning
confidence: 99%
“…The EMA’s Eudravigilance database and the World Health Organization’s Vigibase contain vast numbers of drug reaction reports that can be screened to detect signals. Informal social media reports may uncover novel adverse drug reactions14 and help to understand serious reactions from the patient’s perspective 15…”
Section: How Are New Adverse Drug Reactions Uncovered?mentioning
confidence: 99%
“…The examination of SM utility in identifying AEs and SDRs has been previously performed by multiple groups, using various approaches. Some authors have concluded that SM should be further considered as a potential SD tool, 17,18 while others concluded that SM shows a poor performance in AE and SDR identification. 19,20 Although we count this work among the former group, we do not disagree with the core conclusions of the latter.…”
Section: Discussionmentioning
confidence: 99%
“…18 Data from patient registries and social media are also expected to be utilized in the regulatory process worldwide in the near future. [19][20][21] Information available at the postmarket stage will be changed in line with the social healthcare situation. We need to prepare in response to such changes by utilizing multiple sources of information and data, which depends not mainly on SAERs, to assure drug safety at the postmarket stage.…”
Section: Discussionmentioning
confidence: 99%